2016
DOI: 10.1007/164_2016_126
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation Therapy and NOACs in Heart Failure

Abstract: Current evidence indicates that heart failure (HF) confers a hyper-coagulable state that is associated with adverse events including stroke, systemic embolism, and mortality. This may be due to the elevated levels of pro-thrombotic and pro-inflammatory cytokines that are seen in patients with acute and chronic HF. Left ventricular wall motion abnormalities in patients with systolic dysfunction predispose to local thrombosis due to blood stasis as does atrial fibrillation (AF) which leads to blood stasis in reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Anticoagulants are widely used to prevent ischaemic stroke and other thrombotic events associated with conditions commonly afflicting older adults (eg atrial fibrillation, coronary artery disease, cancer and other hypercoagulable states) 1‐4 . Anticoagulants are also used for treatment of active thrombosis (eg venous thromboembolism) 5,6 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Anticoagulants are widely used to prevent ischaemic stroke and other thrombotic events associated with conditions commonly afflicting older adults (eg atrial fibrillation, coronary artery disease, cancer and other hypercoagulable states) 1‐4 . Anticoagulants are also used for treatment of active thrombosis (eg venous thromboembolism) 5,6 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…The concomitance of both conditions translates into higher morbidity and mortality rates, including a greater risk of thromboembolic events, and consequently, anticoagulation is recommended [6,[11][12][13]. Although a number of studies have analyzed the impact of HF on patients with AF taking vitamin K antagonists, the information currently available among patients treated with direct oral anticoagulants, particularly in clinical practice remains scarce [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the high frequency of thromboembolic complications, embolic prophylaxis with anticoagulants is required in patients with AF with heart failure [7]. It is reported that heart failure is associated with a hypercoagulable state as shown by the elevations of coagulation markers, thrombin/antithrombin complex, prothrombin fragment F1 + 2 (F1+2), and d-dimers [8].…”
Section: Introductionmentioning
confidence: 99%